Mitigation technologies for damage induced by pressure waves in high-power mercury spallation neutron sources (IV) – measurement of pressure wave response and microbubble effect on mitigation in mercury target at J-PARC –. Issue 7 (3rd July 2017) - Kogawa, Hiroyuki; Naoe, Takashi; Futakawa, Masatoshi; Haga, Katsuhiro; Wakui, Takashi; Harada, Masahide; Takada, Hiroshi
ABSTRACT: A mercury target system to produce neutron beams has been operated at the spallation neutron source in the Japan Proton Accelerator Research Complex (J-PARC). Pressure waves are generated in mercury by rapid heat generation due to bombardment by high-intensity short-pulse proton beams. The pressure waves not only cause cyclic stress but also induce the cavitation damage on the target vessel. Reduction of these pressure waves is important from the viewpoint of extending the lifetime of the target vessel in future power-up operations. The injection of microbubbles into mercury is effective for reducing pressure waves. Accordingly, a microbubble generator was installed in the mercury target vessel and an in situ diagnostic system that measures the displacement velocity of the target vessel induced by the pressure waves was also set up in J-PARC to investigate the effect of proton beam condition and the effect of the microbubbles. Consequently, we found that the peak displacement velocity of the target vessel decreased owing to microbubble injection. The ratios of the peaks obtained with bubble injection to that without bubble injection were 1/3 and 2/3 when the injected gas fractions were 0.4% and 0.1%, respectively.